Prevalensi dan Faktor-Faktor Terkait Depresi Postpartum di Kabupaten Buleleng: Prevalence and Associated Factors of Postpartum Depression in Buleleng Regency - Pratiwi, Putu Irma; Sekarini, Ni Nyoman Ayu Desy; Erlian, Ida Ayu (Universitas Ngudi waluyo, 2025)
Postpartum depression (PPD) comprises a cluster of depressive symptoms experienced by women within the first year after childbirth and represents a significant public mental health issue. The objective to determine the prevalence of, and factors associated with, PPD in Buleleng Regency in 2024. A cross-sectional study was conducted among postpartum women within 12 months of delivery between January and August 2024. A total of 317 participants were recruited using purposive sampling based on predefined inclusion and exclusion criteria. The Indonesian version of the Edinburgh Postnatal Depression Scale (EPDS) was used to assess depressive symptoms. Data were analyzed in SPSS. Univariate analyses summarized respondent characteristics and PPD prevalence, while bivariate associations were examined using Chi-square tests and expressed as crude odds ratios (cOR) with 95% confidence intervals (CI). The Results are The highest prevalence of depressive symptoms occurred among women aged >35 years (39.1%), followed by those aged <20 years (22.2%), and was lowest in the 20–35-year group (5.3%). Preterm delivery was strongly associated with PPD compared with term delivery (cOR 61.87; 95% CI 21.25–180.11; p<0.001). Lack of partner support was also associated with higher odds of PPD (cOR 5.49; 95% CI 1.78–16.90; p<0.01). The findings highlight the need for routine EPDS screening, strengthening partner support, and closer monitoring of mothers with obstetric risk factors. Abstrak Depresi Postpartum (DPP) mengikutsertakan beberapa gejala depresi umum yang terjadi pada perempuan ditahun pertama setelah melahirkan dan menjadi masalah kesehatan mental yang signifikan di masyarakat. Penelitian ini bertujuan untuk mengetahui prevalensi dan faktor terkait Depresi Postpartum di Kabupaten Buleleng Tahun 2024. Penelitian ini merupakan jenis penelitian cross sectional dengan populasi ibu nifas dalam 12 bulan terakhir di Kabupaten Buleleng, dilakukan pada Januari sampai Agustus 2024. Jumlah sampel 317 dengan teknik purposive sampling yang memenuhi kriteria inklusi dan eksklusi. Instrumen yang digunakan adalah Edinburgh Postnatal Depression Scale (EPDS) versi Indonesia. Analisa data dilakukan menggunakan program analisis statistik SPSS. Analisis univariat menghitung statistik deskriptif seperti frekuensi dan persentase untuk karakteristik responden dan menentukan prevalensi gejala DPP. Uji bivariat dengan Chisquare dengan hasil prevalensi depresi tertinggi terdapat pada kelompok usia >35 tahun (39,1%), diikuti kelompok usia <20 tahun (22,2%), dan terendah pada kelompok usia 20-35 tahun (5,3%). Ibu dengan preterm memiliki peluang depresi yang jauh lebih tinggi dibanding aterm (cOR 61,87 dengan 95%CI 21-25-180.11; p<0,001). Ketiadaan dukungan pasangan juga berhubungan dengan peluang depresi yang lebih tinggi (cOR 5,49 dengan 95%CI 1,78–16,90; p<0,01). Temuan pada penelitian ini menunjukkan pentingnya skrining rutin (EPDS), penguatan dukungan pasangan, dan pemantauan lebih ketat pada ibu dengan risiko obstetrik.